2012
DOI: 10.1371/journal.pone.0042705
|View full text |Cite
|
Sign up to set email alerts
|

A Lack of Sexual Dimorphism in Width-to-Height Ratio in White European Faces Using 2D Photographs, 3D Scans, and Anthropometry

Abstract: Facial width-to-height ratio has received a great deal of attention in recent research. Evidence from human skulls suggests that males have a larger relative facial width than females, and that this sexual dimorphism is an honest signal of masculinity, aggression, and related traits. However, evidence that this measure is sexually dimorphic in faces, rather than skulls, is surprisingly weak. We therefore investigated facial width-to-height ratio in three White European samples using three different methods of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(97 citation statements)
references
References 25 publications
8
84
4
Order By: Relevance
“…Initial work indicated that fWHR might be sexually dimorphic (Weston, Friday, & Liò, 2007) and linked to pubertal testosterone in men (e.g., Lefevre, Lewis, Perrett, & Penke, 2013); however, more recent work has found little evidence for this putative relationship between fWHR and sex or testosterone (Bird et al, 2016;Hodges-Simeon, Sobraske, Samore, Gurven, & Gaulin, 2016;Kramer, Jones, & Ward, 2012;Lefevre, Etchells, Howell, Clark, & Penton-Voak, 2014;Özener, 2012), suggesting that high versus low fWHR is likely not a sex typical feature.…”
Section: Humanness From Faces: the Case For Facial Width-to-height Ratiomentioning
confidence: 99%
“…Initial work indicated that fWHR might be sexually dimorphic (Weston, Friday, & Liò, 2007) and linked to pubertal testosterone in men (e.g., Lefevre, Lewis, Perrett, & Penke, 2013); however, more recent work has found little evidence for this putative relationship between fWHR and sex or testosterone (Bird et al, 2016;Hodges-Simeon, Sobraske, Samore, Gurven, & Gaulin, 2016;Kramer, Jones, & Ward, 2012;Lefevre, Etchells, Howell, Clark, & Penton-Voak, 2014;Özener, 2012), suggesting that high versus low fWHR is likely not a sex typical feature.…”
Section: Humanness From Faces: the Case For Facial Width-to-height Ratiomentioning
confidence: 99%
“…Of particular note, fWHR has been shown to correlate positively with male strength (Windhager, Schaefer, & Fink, 2011), fighting ability (Zilioli et al, 2015), aggression (Haselhuhn, Ormiston, & Wong, 2015), and perceived dominance (Mileva, Cowan, Cobey, Knowles, & Little, 2014). However, unlike the measure of facial masculinity used by Penton-Voak et al (2001) and Pound et al (2009), fWHR is not reliably sexually dimorphic (Kramer, Jones, & Ward, 2012;Lefevre et al, 2012;Özener, 2012). Moreover, evidence of an association between fWHR and testosterone levels is equivocal (Hodges-Simeon et al, 2016;Lefevre, Lewis, Perrett, & Penke, 2013).…”
Section: The Current Studymentioning
confidence: 97%
“…In a similar study conducted by Hewig et al, in which participants were presented with pictures of dressed women and men, the male participants' initial look was at the face of women, followed by fixation on the breasts [21]. The face is another important influence on attractiveness ratings, as it transmits a variety of information including sociodemographic information such as gender or age, but also information on emotions and physical health [22][23][24]. Familiarity has been shown to be another important aspect for attractiveness ratings, as we react positively to known things [25].…”
Section: Sex and Attractionmentioning
confidence: 99%